News media innovation reconsidered ethics and values in a creative reconstruction of journalism - Cruz, María Luengo 1972-; Herrera-Damas, Dácil Susana 1976- (Hoboken, New Jersey Wiley Blackwell, 2021)
News media are suffering a Schumpeterian "creative destruction" (Schumpeter, 1949): this has been the received wisdom among scholars and media watchers evaluating the impact of digital technology on journalism today. However, is "creative destruction" an appropriate term in this case? The use of it to explain this recent period of upheaval in journalism usually involves reductive techno-economic paradigms that overlook critical cultural and ethical dimensions. This collective volume aims to understand technological innovation as "creative reconstruction" (Alexander, 2016). The idea of "creative reconstruction" was coined by cultural sociologist Jeffrey C. Alexander around 2014, after he and a group of cultural sociologists and journalism scholars expressed frustration at how academics and pundits were narrowly theorizing in purely technological and economic terms the current "crisis of journalism" and the consequent changes and innovations in news. This perspective was crystalized in The Crisis of Journalism Reconsidered (Alexander, Breese, and Luengo, 2016), a book that shows how crisis and change in journalism are equally caused by cultural and ethical factors. The empirical investigations in The Crisis of Journalism Reconsidered demonstrate that intense alarm over digital change implies the strength of both journalistic ethics and democratic values (Carlson, 2016; Luengo, 2016). The book argues that the compulsion to defend these ethical and civil commitments actually energizes a search for new organizational and technological forms.
Introduction : Journalism's creative reconstruction : how innovation in news is embracing enduring professional and civil values -- Journalism, ethics, and innovation in times of digital turbulence -- An Inquiry into the ethics of innovation in digital journalism -- Democratically engaged journalists : ethical invention amid unreasonable publics -- Journalism innovation in a time of survival -- New ethics and emerging journalistic narratives -- Ethics in 360-degree immersive journalism -- Quo vadis, newsgames? Ethical boundaries between journalism and games -- Guiding the adoption of news storytelling design through ethics : the use of stories in Google's AMP project -- Interrogating data, algorithms, and automatization through journalism ethics -- Data journalism, massive leaks, and investigation : what the Panama papers have taught us about ethics -- Semi-automated journalism : reinforcing ethics to make the most of artificial intelligence for writing news -- Ethical challenges in incorporating artificial intelligence into newsrooms -- Journalistic innovation at the service of the public -- Journalism, algorithms, and the people's right to know -- Ethical dilemmas in the personalization of news from voice interfaces -- Transparency, innovation, and journalism -- Innovative tools for citizen empowerment in the fight against misinformation -- Conclusion.
Includes bibliographical references, appendix and index (pages 228-237).
Purchased: Golden Books (17 September 2022); Selected at the Manila International Book Fair 2022.
Keywords: Journalistic ethics; Journalism -- Social aspects; Journalism -- Technological innovations